Romanticism : an Oxford guide - Roe, Nicholas (Oxford : New York ; Oxford University Press, 2005)
"This book is a guide of the Romantic field. It includes 46 chapters offering background and contextual information with detailed readings of Romantic texts. The volume is divided into four parts - 'Romantic Orientations', 'Reading Romanticism', 'Romantic Forms' and 'Romantic Afterlives'" --Provided by publisher.
Includes bibliographical references and index.
Keywords: English literature -- 19th century -- History and criticism -- Handbooks, manuals, etc; English literature -- 18th century -- History and criticism -- Handbooks, manuals, etc; Romanticism -- Great Britain -- Handbooks, manuals, etc